Metronomic Temozolomide in Heavily Pretreated Patients With Recurrent Isocitrate Dehydrogenase Wild-type Glioblastoma: A Large Real-Life Mono-Institutional Study. Issue 5 (May 2023) - Bosio, A.; Cerretti, G.; Padovan, M.; Caccese, M.; Denaro, L.; Chioffi, F.; Della Puppa, A.; Aldegheri, V.; Guarneri, V.; Zagonel, V.; Lombardi, G.
Abstract: Aims: Glioblastoma (GBM) is the most common primary malignant brain tumour in adults and frequently relapses. The aim of this study was to assess the efficacy and safety of metronomic temozolomide (TMZ) in the recurrent GBM population. Materials and methods: All patients treated at our centre between September 2013 and March 2021 were retrospectively reviewed. The main inclusion criteria were first-line therapy with the Stupp protocol, relapse after the first or subsequent line of therapy, treatment with a metronomic TMZ schedule (50 mg/m 2 continuously) and histological diagnosis of isocitrate dehydrogenase wild-type GBM according to World Health Organization 2016 classification. Results: In total, 120 patients were enrolled. The median follow-up was 15.6 months, the median age was 59 years, Eastern Cooperative Oncology Group performance status (ECOG-PS) was 0–2 in 107 patients (89%). O 6 -methylguanine-DNA-methyltransferase (MGMT) was methylated in 66 of 105 (62%) evaluable patients. The median number of prior lines of treatment was 2 (range 1–7). Three (2%) patients showed a partial response; 48 (40%) had stable disease; 69 (57%) had progressive disease. The median overall survival from the start of metronomic TMZ was 5.4 months (95% confidence interval 4.3–6.4), whereas the median progression-free survival (PFS) was 2.6 months (95% confidence interval 2.3–2.8). At univariate analysis, MGMT methylated and unmethylated patients had a median PFS of 2.9 and 2.1 months ( P = 0.001) and a median overall survival of 5.6 and 4.4 months ( P = 0.03), respectively. At multivariate analysis, the absence of MGMT methylation (hazard ratio = 2.3, 95% confidence interval 1.3–3.9, P = 0.004) and ECOG-PS ≤ 2 (hazard ratio = 0.5, 95% confidence interval 0.3–0.9, P = 0.017) remained significantly associated with PFS, whereas ECOG-PS ≤ 2 (hazard ratio = 0.4, 95% confidence interval 0.3–07, P = 0.001) was the only factor associated with overall survival. The most common grade 3–4 toxicities were haematological (lymphopenia 10%, thrombocytopenia 3%). Conclusions: Rechallenge with metronomic TMZ is a well-tolerated option for recurrent GBM, even in pretreated patients. Patients with methylated MGMT disease and good ECOG-PS seem to benefit the most from this treatment. Highlights: Glioblastoma is the most common primary brain tumour in adults. There is no general consensus about the best therapy at relapse. Temozolomide at 50 mg/m 2 continuously can be a viable therapeutic option for recurrent glioblastoma patients. Heavily pretreated patients could benefit from metronomic temozolomide with a satisfying safety profile.